SUSTAINABILITY OF PRODUCTION, SALES, AND PRICES OF HERBAL DRINK PRODUCTS DEVELOPED BY THE CENTER FOR AGROTECHNOLOGY INNOVATION (PIAT) UGM: A BREAK-EVEN POINT APPROACH - Hani Perwitasari; Fatkhiyah Rohmah; Triya Andriyani (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
The growing public interest in herbal beverages presents an opportunity for the Center for Agrotechnology Innovation of UGM (PIAT) to develop instant herbal beverage products. The PIAT-produced herbal drinks items Rosegar (rosella drink), Segar Ayu (wedang uwuh fresh drink), and Gilegrass (citronella ginger powder drink) all already have the Food and Drug Administration (BPOM) certificates. However, the three products have not yet achieved optimal sales, and it is necessary to evaluate the sustainability of production, sales, and prices of these products using a Break Even Point (BEP) analysis approach. Therefore, the goal of this study is to determine whether the BEP of the three products can be achieved. The analysis is performed for a single month of production in 2022. The study results show that the BEP for the production of Rosegar is 136 bottles, the BEP for sales is Rp. 1,364,385 at Rp. 4,586 and the BEP for the production of Segar Ayu and Rosella is 98 packs, the BEP for sales is Rp. 2,951,025 at Rp. 23,208. Overall, the price of PIAT’s herbal drink products is already higher than that of BEP, but production and sales remain low or non-optimal.